Autoinflammation and autoimmunity across rheumatic and musculoskeletal diseases - Szekanecz, Zoltan; Mcinnes, Iain B.; Schett, Georg; Szamosi, Szilvia; Benko, Szilvia; Szucs, Gabriella (Nature Reviews Rheumatology, 2021)
Most rheumatic and musculoskeletal diseases (RMDs) can be placed along a spectrum of disorders, with autoinflammatory diseases (including monogenic systemic autoinflammatory diseases) and autoimmune diseases (such as systemic lupus erythematosus and antiphospholipid syndrome) representing the two ends of this spectrum. However, although most autoinflammatory diseases are characterized by the activation of innate immunity and inflammasomes and classical autoimmunity typically involves adaptive immune responses, there is some overlap in the features of autoimmunity and autoinflammation in RMDs. Indeed, some ‘mixed-pattern’ diseases such as spondyloarthritis and some forms of rheumatoid arthritis can also be delineated. A better understanding of the pathogenic pathways of autoinflammation and autoimmunity in RMDs, as well as the preferential cytokine patterns observed in these diseases, could help us to design targeted treatment strategies.
CRIS-Team Scopus Importer:2021-08-13